Clinical impact of early bronchoscopy in mechanically ventilated patients with aspiration pneumonia. Issue 7 (6th July 2015) - Lee, Hyun Woo; Min, Jinsoo; Park, Jisoo; Lee, Yeon Joo; Kim, Se Joong; Park, Jong Sun; Yoon, Ho Il; Lee, Jae‐Ho; Lee, Choon‐Taek; Cho, Young‐Jae
Abstract Background and objective A handful of studies have reported that bronchoscopies influence the clinical outcome of mechanically ventilated patients with aspiration pneumonia. The purpose of the present study is to elucidate the therapeutic role of early bronchoscopy in patients with aspiration who are mechanically ventilated. Methods A retrospective cohort study was conducted via medical record review from 2003 through 2013 in a tertiary hospital. All the diagnoses of pneumonia were supported by the probability of aspiration and consolidation of dependent areas confirmed by computed tomography. Patients who underwent bronchoscopy within 24 h after intubation were categorized as the early bronchoscopy group and the others as the late bronchoscopy group. We compared the demographics, clinical parameters and outcomes between the two groups. Results Of the 154 patients who were included, the early bronchoscopy group (n = 93) showed significantly lower in‐intensive care unit (ICU) mortality and 90‐day mortality (in‐ICU: 4.9% vs 24.6%; 90‐day: 11.8 vs 32.8%) regardless of the initial empirical antibiotics. In addition, their sequential organ failure assessment score on day 7 tended to decrease more rapidly. Among the survivors, patients in the early bronchoscopy group were extubated earlier with a higher success rate, had a shorter length of mechanical ventilation and had a shorter ICU stay. The early bronchoscopy was associated with lower 90‐day mortality in multivariate analysis (odds ratio: 0.412; 95% confidence interval: 0.192–0.883). Conclusions Early bronchoscopy could benefit the clinical outcomes of mechanically ventilated patients with aspiration pneumonia.